Microstructural Analysis of Silica Fume Concrete with Scanning Electron Microscopy and X-Ray Diffraction - Uzbas, B.; Aydin, A. C. (Engineering, Technology & Applied Science Research, 2020)
The effects of using different ratios of silica fume on the mechanical and microstructural properties of hardened cement paste and concrete were investigated in this study. Portland cement was replaced with 5%, 10%, 15%, and 20% silica fume (SF) by weight. Microstructural properties of obtained samples were investigated by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD analysis showed that the ratio of calcium hydroxide (CH), which is produced by hydration, decreases depending on the concrete age and the amount of silica fume. The SEM analysis showed that the use of silica fume decreases gaps and calcium silicate hydrate (C-S-H) which is also a hydration production. Silica fume content of up to 15% improved the observed mechanical and microstructural properties of concrete. At the optimum value of 15%, improvement in the paste was observed due to the filler effect and the reaction between the silica fume and calcium hydroxide, leading to a reduction in calcium hydroxide in the concrete.